Numerical and Experimental Study on RC Exterior Beam-Column Joint with Beam Weak in Flexure - Mounica, K; Polu Raju, P (International Journal of Engineering and Technology, 2018)
When the structures are subjected to seismic forces, beam-column joint (BCJ) is the most affected portion of the structure. External BCJs are more vulnerable than interior BCJs. In this present study, both numerical and experimental study has been carried out on external BCJ to assess the structural behavior. The numerical analysis of the BCJ is done in ANSYS (finite element based) and the experimental study is carried out on loading frame. Three specimens were designed according to IS 456:2000. Out of three, the first specimen was provided with 100% flexural reinforcement as per design, whereas second and third specimens were reduced with 40% and 50% flexural reinforcement as a parameter of beam weak in flexure when compared with the first specimen. The fourth specimen was designed according to IS 13920:2016to achieve the appropriate ductility. All four external BCJs were tested under monotonic tip loading applied on beam and the support conditions are hinged at both ends of the column. These specimens are designed to achieve the strong column-weak beam concept. The deflection, crack pattern and stress intensity are observed and recorded.Â